Gestión del agua de las microcuencas el Dedito y San Antonio del piedemonte andino – amazónico desde la perspectiva del desarrollo sostenible - Donovan Godoy Lozada; Douglas Izarra Vielma (Mundo Fesc)
Water should be viewed from the perspective of the common interest rather than the private, with communities and other entities involved in its use, management, and conservation. However, the pressure of inadequate demand for this resource for human and productive consumption constitutes one of the most significant threats to the sustainability of water resources, linked to population growth. This phenomenon is addressed in the western commune of the municipality of Florencia (Caquetá, Colombia). The residents of the El Timmy neighborhood were forced to tap into the waters of the micro-basins of the El Dedito and San Antonio streams. This process is analyzed in the present study, which, applying the Grounded Theory method and the focus group technique, describes the actions taken by the user community regarding access to and use of water from a sustainable development perspective. The results reveal inefficient or insufficient action by the state and the actions of the people themselves to address their need for access to and use of water. Demonstrating the importance of education for sustainable development, enabling them to organize and claim their right to water, and in turn, to make their actions sustainable in relation to their health care and the water resource itself. Among some conclusions, education for sustainable development is a necessity in all areas, not just in schools; it is even more necessary in communities with the involvement of educational institutions.